Anthocyanin level and organoleptic preference level of sweet potato (Ipomoea batatas) and red beans (Phaseolus vulgaris) muffin as high anthocyanin snack: Kadar Antosianin dan Tingkat Kesukaan Muffin Ubi Ungu (Ipomoea batatas) dan Kacang Merah (Phaseolus vulgaris) Sebagai Kudapan Tinggi Antosianin - Al-Munadia; Aprilia, Veriani; Salfarino, Ryan (Universitas Slamet Riyadi Surakarta, 2025)
Diabetes Mellitus is a metabolic disorder marked by hyperglycemia resulting from the body's failure to synthesize insulin. Nutritional therapy is effective in controlling glucose levels by providing low glycemic index and high in antioxidant foods, including sweet potatoes and red beans. The primary objective of this study was to elucidate the influence of wheat flour replacement with composite flour consisting of sweet potato and red bean flour on anthocyanin content and the sensory preferences of muffins. A single-factor completely randomized approach was used in this experimental investigation. The treatment involved substituting wheat flour with a composite flour consisting of sweet potato and red bean flours, in the following ratios: 30:20:50 (F1), 30:35:35 (F2), 30:50:20 (F3), and 100:0:0 (F0, control). Anthocyanin content was analyzed using the differential pH method, while sensory preferences were evaluated by 30 semi-trained panelists using a hedonic scale test. The results showed that substituting wheat flour with composite flour high in sweet potato content increased anthocyanin levels. However, the substitution of wheat flour generally reduced the overall sensory preference for muffins. Despite this, formulations with a higher proportion of sweet potato flour improved the preference scores. In conclusion, the substitution of wheat flour with composite flour rich in sweet potato increased anthocyanin content and improved sensory preferences for color, aroma, and taste in muffins